Effect Of Work Motivation And Work Discipline On The Performance Of Personnel Division Employees At PT. Beton Perkasa Wijaksana - Ruth Mahdalena; Herayati Herayati; Martinus Wahyu Purnono (Trigin Publisher, 2023)
Human resources are a driving factor in the running of the organization's operations, the success of the organization is determined by the existence of its human resources. So that human resources or organizational employees are the main concern for achieving organizational success. The achievement of these goals is influenced by several factors, namely work motivation and work discipline. This research approach uses an associative approach, with the aim of analyzing the problem of the relationship between a variable and other variables. Total sampling is taken from the whole in the study. So that the sample used in this study was as many as 35 employees of the personnel division at PT. Beton Perkasa Wijaksana. Methods of analysis, Quantitative Analysis, Classical Assumption Test, t test, and F test. The results of multiple linear regression equations Y 9,569 + 0,39X1 + 0,390X2